2014
DOI: 10.1002/pmh.1273
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between expressed emotion and wellbeing for families and carers of a relative with Borderline Personality Disorder

Abstract: Background: Previous research has found that family environments high in expressed emotion, in particular emotional overinvolvement, are beneficial to the clinical outcome of patients with Borderline Personality Disorder (BPD). Aim: This study aims to investigate the relationship between expressed emotion, carer burden and carer wellbeing. Method: A total of 280 carers of a relative with BPD were administered the McLean Screening Instrument for BPD -Carer Version, The Family Questionnaire, Burden Assessment Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
40
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 55 publications
11
40
0
2
Order By: Relevance
“…Regarding our second aim, associations were found between consequences of caregiving and LEE scores: urging (IEQ) was positively associated with intrusiveness (EE) and hostility towards the patient (EE), and tension (IEQ) was negatively associated with coping with illness (EE) and positively with hostility towards the patient (EE); however, all the correlations were moderate to low. These results are similar to other studies where higher emotional overinvolvement was correlated with greater burden in caregivers of patients with BPD diagnoses (Bailey & Grenyer, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Regarding our second aim, associations were found between consequences of caregiving and LEE scores: urging (IEQ) was positively associated with intrusiveness (EE) and hostility towards the patient (EE), and tension (IEQ) was negatively associated with coping with illness (EE) and positively with hostility towards the patient (EE); however, all the correlations were moderate to low. These results are similar to other studies where higher emotional overinvolvement was correlated with greater burden in caregivers of patients with BPD diagnoses (Bailey & Grenyer, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…However, consumers with personality disorder often are not offered or are unable to access evidence-based therapies and thus have negative experiences when receiving mental health services [6]. In addition, carers supporting consumers with personality disorder often experience high levels of stress, grief, and mental health problems [7,8], and they can experience difficulties accessing appropriate services for themselves and the consumers they support [9]. Considering the perspectives of consumers and carers is recommended to improve mental health services [10], and is supported by government [11,12] and mental health professionals [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study on caregiving relatives of people with BPD is largely consistent, although the sample was more evenly split between parents and significant others (Bailey & Grenyer, 2015). More than half of relatives surveyed reported that they were their loved ones' primary caregiver and just over half resided with their loved one (Bailey & Grenyer, 2015). The study of caregivers of people with personality disorders has largely focused on those caring for people with BPD (Bailey & Grenyer, 2013).…”
Section: Characteristics Of Caregivers Until Recently Caregivers Ofmentioning
confidence: 96%
“…A systematic review of six studies found that such caregivers had a mean age of 51, almost 90% were the care-receivers' parents, and more than half of those were mothers (Bailey & Grenyer, 2013). A more recent study on caregiving relatives of people with BPD is largely consistent, although the sample was more evenly split between parents and significant others (Bailey & Grenyer, 2015). More than half of relatives surveyed reported that they were their loved ones' primary caregiver and just over half resided with their loved one (Bailey & Grenyer, 2015).…”
Section: Characteristics Of Caregivers Until Recently Caregivers Ofmentioning
confidence: 99%